Bonds and bridges: perspectives of service-engaged young people on the value of relationships in addressing alcohol and other drug issues - Green, Rachael; Mitchell, Penelope; Bruun, Andrew (Routledge, 2013)
This study draws on the qualitative data with 42 currently engaged clients of an Australian youth alcohol and other drug (AOD) service. We explore young people's perspective on the function of relationships in relation to the aetiology and resolution of their significant issues. Three relationship types are central: those with family, peers and youth service providers. Young people perceived that family and peer relationships were strongly implicated in their difficulties with AOD use, offending behaviour and emotional well-being. This is consistent with a strong evidence base for the effectiveness of family and social network focused interventions. The construct of social capital and its central metaphor of ‘bonding’ and ‘bridging’ offers a useful schema for conceptualising the function of the therapeutic relationship in strengthening young people's natural social relationships and assisting them to form new connections that may offer and new resources and opportunities consistent with their goals.